Systematic risk factors in stock pricing modeling: A new theoretical conceptualization. - Tuyon, Jasman; Ahmad, Zamri (Universiti Sains Malaysia, 2014)
Stock pricing modeling in both modern- and behavioral finance paradigms are remain divided, still incomplete and have been criticized for some philosophical, theoretical and model limitations. These cause the identification of risk factors in stock pricing modeling to remain puzzling. This analytical conceptual paper aims to address these issues with a new theoretical conceptualization of the risk factors in stock pricing modeling.